Circulating Nucleic Acids in Plasma or Serum (CNAPS) as Prognostic and Predictive Markers in Patients with Solid Neoplasias. Issue 3 (9th June 2013) - Goebel, Georg; Zitt, Marion; Zitt, Matthias; Müller, Hannes M.
Abstract : It is now widely accepted that there is a need for the development of molecular markers of cancer that can be used for clinical prognostication and monitoring. Approximately a decade ago tumor-derived circulating nucleic acids in the plasma or serum (CNAPS) of cancer patients were introduced as a noninvasive tool for cancer detection. This review focuses on the various types of CNAPS of patients with solid neoplasias (genetic alterations in circulating DNA, microsatellites, methylated DNA, viral DNA, nucleosomes, mitochondrial DNA and cell-free mRNA) and their putative potential as prognostic or predictive parameter or even as a tool for therapy monitoring during follow-up. Additionally, this review aims to point out the difference between a prognostic and a predictive factor in patient bloodstream. However, with rapid technical improvement and well-designed studies we conclude that the next years will see CNAPS analysis integrated in the prognostication and monitoring of cancer patients, thus producing more specific treatment regimens for patients with various stages of neoplastic disease and ultimately longer survival and better quality of life.